SAT0236 Role of serological markers at baseline and follow-up in predicting biopsy proven lupus nephritis. (23rd January 2014) - Chanchlani, N.; Gayed, M.; Yee, C.-S.; Gordon, C.
Abstract : Background: Studies have shown that 30-50% of SLE patients (pts) develop lupus nephritis (LN). Patients with high affinity anti-dsDNA antibodies (abs) are more likely to develop LN. The Farr radioimmunoassay is the best method of detecting these abs but is rarely available. Instead ELISA tests for anti-dsDNA abs that detect abs of variable affinity and Crithidia test for high affinity abs are used. It is unclear if the Crithidia test needs to be repeated at every visit with C3 and C4 & anti-dsDNA abs by ELISA to assess lupus activity and the risk of developing LN. Objectives: To audit the relationship between anti-dsDNA abs by ELISA & Crithidia, & low C3 & C4 at baseline & follow-up in SLE pts with and without biopsy proven LN. Methods: Data was recorded prospectively from 1989 including lupus activity, renal biopsy (WHO classification), anti-dsDNA abs by ELISA & Crithidia, C3 and C4 levels. Pts were excluded if not seen in the clinic before 1st renal biopsy, had <2 visits to the clinic or had missing baseline &/or followup data. Pts that developed Class III/IV ±class V were combined. Pure class V LN was analysed separately. Results: Of 309 pts, 290 (94%) were eligible: 93%female, 7% male, 12.7% Afro-Caribbean, 17% South Asian, 63%Caucasian, 2% Chinese & 3% recorded as mixed/other. The mean±sd age was 49±15.1 & disease duration 17.5±8.3 years. There were 43 eligible pts with renal biopsies. Distribution of each WHO class of LN was Class II 16%, Class III/IV 63%, and Class V 9%. The 27 pts that developed Class III/IV LN (LNIII/IV) were compared with remaining 263 pts. At baseline, 78% of LN III/IV patients had anti ds-DNA abs by ELISA and Crithidia, vs 20% positive (pos) for both without LN III/IV, see table 1; 81% of LN III/IV were pos for each anti-DNA abs test vs 33% without LN III/IV ELISA pos and 22% Crithidia pos. Low C3 & C4 was present in 63% with LN III/IV and 7% without LN III/IV, and 63% with LN III/IV had pos ELISA & low C3/C4 vs 5% without LN III/IV. Pos ELISA, Crithidia and low C3/C4 was found in 78% with LN III/IV vs 5% without LN III/IV. There was no significant relationship between any anti-dsDNA antibody or complement test singly or in combination at baseline and the subsequent development of class V lupus nephritis. Over time more patients developed anti-dsDNA abs measured by ELISAand Crithidia. Developing Crithidia pos later was not helpful in identifying those more at risk of LN III/IV than baseline measurement. The combination of anti-dsDNA by ELISA with low C3/C4 was sensitive for identifying those at risk of LN III/IV. Conclusions: This audit suggests that the combination of anti-ds DNA abs by ELISA and Crithidia together with low C3/C4 results at baseline can help to identify patients at most risk of developing class III/IV LN. Results do not support the need to measure anti-dsDNA abs by Crithidia serially, but do support the combination of ELISA, C3 & C4. Disclosure of Interest: None Declared